2011
DOI: 10.1016/j.cub.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Regenerant Arabidopsis Lineages Display a Distinct Genome-Wide Spectrum of Mutations Conferring Variant Phenotypes

Abstract: SummaryMulticellular organisms can be regenerated from totipotent differentiated somatic cell or nuclear founders [1–3]. Organisms regenerated from clonally related isogenic founders might a priori have been expected to be phenotypically invariant. However, clonal regenerant animals display variant phenotypes caused by defective epigenetic reprogramming of gene expression [2], and clonal regenerant plants exhibit poorly understood heritable phenotypic (“somaclonal”) variation [4–7]. Here we show that somaclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 37 publications
13
91
4
Order By: Relevance
“…Finally, mutations that exhibited a heterozygous pattern (e.g., where 20%-80% of reads showed a base different from the reference base) or where there was insufficient coverage in G0 or G10 were also excluded from the final mutation lists. Our previous studies confirmed that ;100% of the mutations detected by the above described multistep variant detection pipeline were real (Jiang et al 2011;Belfield et al 2012). Using this pipeline, we identified 102 and 52 mutations in G10 saline soil and control samples, respectively (Supplemental Tables S2, S3).…”
Section: Salt Content Determinationsupporting
confidence: 58%
See 2 more Smart Citations
“…Finally, mutations that exhibited a heterozygous pattern (e.g., where 20%-80% of reads showed a base different from the reference base) or where there was insufficient coverage in G0 or G10 were also excluded from the final mutation lists. Our previous studies confirmed that ;100% of the mutations detected by the above described multistep variant detection pipeline were real (Jiang et al 2011;Belfield et al 2012). Using this pipeline, we identified 102 and 52 mutations in G10 saline soil and control samples, respectively (Supplemental Tables S2, S3).…”
Section: Salt Content Determinationsupporting
confidence: 58%
“…The transition/transversion (Ti/Tv) ratio of single base substitutions accumulating in A. thaliana MA lineages exposed over multiple successive generations to soilsalinity stress (;1.7) is different from that of control MA lineages (;2.5) (Fig. 1C), but similar to that of mutations accumulated in in vitro regenerant or irradiated A. thaliana lineages (Jiang et al 2011;Belfield et al 2012). Intriguingly, the change in Ti/Tv ratio generated by salt stress in A. thaliana is similar to that generated by the environmental stress response in yeast (Shor et al 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1d) appear to be in the middle between those reported for spontaneous mutations (2.41-2.73 (Ossowski et al, 2010)) and fast-neutron-induced mutations (0.86 (Belfield et al, 2012)) in Arabidopsis plants. The Ti/Tv ratios are slightly lower than those reported for ethylmethane sulfonate (EMS) mutagenesis (1.63-1.83 (MohdYusoff et al, 2015)) and greater than those in regenerated plants of rice (1.1 (Miyao et al, 2012)) and Arabidopsis (0.92 (Jiang et al, 2011)). These differences must be related to the nature of mutagens, but the underlying mechanism awaits further study.…”
Section: Type Of γ Irradiation-induced Mutationsmentioning
confidence: 60%
“…These procedures produced regenerated plants (R1), and the next generation phase (R2) was obtained from seeds that were collected from the R1 regenerants. The pH of all media was adjusted to 5.8 and autoclaved at 121°C for 20 min (Jiang et al 2011). Control plants were grown on a hormone-free MS medium in the same conditions as the plants used as the source of explants.…”
Section: Plant Materials and In Vitro Culturementioning
confidence: 99%